Near surface ground temperature, soil moisture and snow depth measurements in the Kaldoaivi Wilderness Area, for 2016-2018 - Helena Bergstedt; Annett Bartsch (PANGAEA, 2020)
iButton (24) loggers measuring soil temperature were deployed in the Kaldoaivi Wilderness Area in August/September 2016 and retrieved in August 2018. They were installed in a very shallow depth in different locations, covering a wide range of landscape types, exposure and suspected snow conditions. Sensors were deployed approximately 3-5cm below the surface to avoid direct influence by the sun. Near surface soil moisture measurements were taken during late August/early September of 2016, 2017 and 2019 at the locations of the deployed iButtons. Snow depth and snow water equivalent measurements were taken during March 2018 at or near most measurement points. The field work and research was supported by the Austrian Science Fund (Fonds zur Förderung der wissenschaftlichen Forschung, FWF) through the Doctoral College GIScience (DK W1237-N23).